1993
DOI: 10.1104/pp.101.1.313
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Indole-3-Acetic Acid (IAA) in Wild-Type and IAA-Overprodcing Transgenic Tobacco Plants, and Identification of the Main Conjugates by Frit-Fast Atom Bombardment Liquid Chromatography-Mass Spectrometry

Abstract: Transgenic plants overproducing indole-3-acetic acid (IAA) from expression of the Agrobacterium tumefaciens T-DNA IAA biosynthesis genes were used to study the conjugation of IAA. At the 11-node stage, free IAA, as well as ester-and amide-conjugated IAA, was analyzed in wild-type tobacco SR1 and in transgenic plants denoted 35S-iaaMliaaH (line C) and 35s-iaaM X 35s-iaaH ( l h e X). The transgenic plants contained increased levels of both free and conjugated IAA, and the main increase in IAA conjugates occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…However, a subsequent study has shown that the major IAA conjugates in tobacco are the amide derivatives IAAsp and indole-3-acetylglutamic acid. IAGluc was not detected and the ester conjugates are restricted to a minor component with similar polarity characteristics to IAlnos (Sitbon et a/., 1993). In the present investigation, it was observed that rolB leaves contained 30% less conjugated IAA than that of wild-type leaves (Figure 3b).…”
Section: There Is No Difference In the Capacity Of Rolb And Wild-typesupporting
confidence: 44%
“…However, a subsequent study has shown that the major IAA conjugates in tobacco are the amide derivatives IAAsp and indole-3-acetylglutamic acid. IAGluc was not detected and the ester conjugates are restricted to a minor component with similar polarity characteristics to IAlnos (Sitbon et a/., 1993). In the present investigation, it was observed that rolB leaves contained 30% less conjugated IAA than that of wild-type leaves (Figure 3b).…”
Section: There Is No Difference In the Capacity Of Rolb And Wild-typesupporting
confidence: 44%
“…The effects of iaaM expression on postembryonic development have been described in detail for Arabidopsis (Romano et al, 1995), tobacco (Nicotiana tabacum; Sitbon et al, 1992), and petunia (Petunia hybrida; Klee et al, 1987). In accordance with these studies, hypocotyl elongation was strongly enhanced in proLTP1iaaM seedlings (the notation proXY describes transactivation of gene Y by promoter X; average hypocotyl length 1.66 6 0.24 mm [n ¼ 26] in the wild type, 4.61 6 0.86 mm [n ¼ 30] in proLTP1iaaM; Figure 1A).…”
Section: Manipulation Of Auxin Homeostasismentioning
confidence: 99%
“…This observation is also consistent with the general belief that auxin conjugation plays an important role in controlling the level of active auxin. In plants in which bacterial auxin biosynthesis genes are expressed under the control of their own or strong heterologous promoters, an increase in both free and conjugated auxin has been detected (Klee et al, 1987;Sitbon et al, 1991Sitbon et al, , 1992Sitbon et al, , 1993Romano et al, 1993). It is thus most probable that the increase in auxin conjugate levels in the surl mutant is a consequence of elevated free auxin levels.…”
Section: Linkage Analysismentioning
confidence: 99%
“…The development of molecular biology and gene transfer technology has made it possible to study the physiological effects of elevated endogenous auxin levels. The expression of bacterial auxin biosynthesis genes in plants results in the overproduction of both indole-3-acetic acid (IAA) and IAA conjugates (Klee et al, 1987;Sitbon et al, 1991Sitbon et al, , 1992Sitbon et al, , 1993Romano et al, 1993). The expression of the bacterial IAAlysine synthetase gene leads to the accumulation of IAA conjugates in plants but not necessarily to a comparable decrease in the level of free IAA (Romano et al, 1991;Spena et al, 1991).…”
Section: Introductionmentioning
confidence: 99%